Cases on Technologies in Education From Classroom 2.0 to Society 5.0 - Bishop, Jonathan, 1979-, editor 651821; IGI Global (Online service) 631983 (Hershey, PA : IGI GLOBAL, 2022)
As the use of technology spreads throughout communities, it is a natural progression that those resources will be given to classrooms. In order to provide the best education possible, all resources must be used. Learning, however, is not only done within the classroom; community learning (such as Society 4.0 and Society 5.0) involves remote learning and learning in the community. Cases on Technologies in Education From Classroom 2.0 to Society 5.0 presents case studies on the best practices from practitioners using future technologies for education beyond the classroom. The content within the book specifically includes Classroom 2.0 (networking of education institutions and learners), School 3.0 (situated learning in community venues beyond the classroom), Society 4.0 (sharing education practice and delivering learning remotely), and Society 5.0 (ubiquitous education in smart cities, towns, and villages). Covering topics such as cross-community education, ed-tech, and innovation paths, this book is an in-depth reference for administrators, schools, colleges, and universities looking to embed technology into the way they deliver education, as well as educational software developers, IT consultants, researchers, students, academicians, and teachers looking to enhance the way they educate their learners through technology.